2009
DOI: 10.1002/app.31238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of addition of acrylic compatibilizer on the morphology and mechanical behavior of amorphous polyamide/SAN blends

Abstract: Amorphous polyamide (aPA)/acrylonitrilestyrene copolymer (SAN) blends were prepared using methyl methacrylate-maleic anhydride copolymer MMA-MA as compatibilizer. The aPA/SAN blends can be considered as a less complex version of the aPA/ABS (acrylonitrilebutadiene-styrene) blends, due to the absence of the ABS rubber phase in the SAN material. It is known that acrylic copolymer might be miscible with SAN, whereas the maleic anhydride groups from MMA-MA can react in situ with the amine end groups of aPA during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The synthesis procedure was performed in a reactor under intensive mixing at 70 °C and nitrogen atmosphere for 5 h. The obtained product was precipitated in methanol to remove the major part of non-reacted DMSO and MA. Finally, the MMA-MA was filtrated and posteriorly dried in a forced air circulation oven at 50 °C for 24 h 10,19 . The effective incorporated MA content was determined by conductometric titration with sodium hydroxide (NaOH) 1 M solution as formerly described by Huang et al…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis procedure was performed in a reactor under intensive mixing at 70 °C and nitrogen atmosphere for 5 h. The obtained product was precipitated in methanol to remove the major part of non-reacted DMSO and MA. Finally, the MMA-MA was filtrated and posteriorly dried in a forced air circulation oven at 50 °C for 24 h 10,19 . The effective incorporated MA content was determined by conductometric titration with sodium hydroxide (NaOH) 1 M solution as formerly described by Huang et al…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis was carried out in a reactor under intensive mixing at 70 °C and inert nitrogen atmosphere for 5 h. Subsequently, the product obtained was precipitated in methanol to remove all nonreacted DMSO and MA. After separation and filtration, the MMA‐MA was dried in a forced air circulation oven at 50 °C for 24 h. The synthesis procedure used in this study was based on similar techniques previously reported in literature …”
Section: Methodsmentioning
confidence: 99%
“…After separation and filtration, the MMA-MA was dried in a forced air circulation oven at 50 8C for 24 h. The synthesis procedure used in this study was based on similar techniques previously reported in literature. 25,26 The polymeric mixtures were prepared in a co-rotating twinscrew extruder manufactured by B&P Process Equipment and Systems (L/D 5 25, D 5 19 mm), with temperature profile of 200/220/220/220/230 8C operating at screw speed of 160 RPM. The twin-screw profile used during melt blending process can be observed in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the functional groups was kept constant; therefore, an increase in the concentration of the dispersed phase resulted in a proportional increase in MGE. The melt viscosity increased significantly in comparison to that of the noncompatibilized blend; this promoted changes in the viscosity ratio of the blend components . At high viscosity ratios, the viscous forces that broke the particles were lower than the interfacial forces that maintained the intact particles; this hampered the deformation and breakage of the particles.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, studies devoted to the control of the morphology of polymer blends have drawn plenty of interest in recent decades . Changes in the mechanical properties and brittle ductile behavior due to compatibility and/or morphology have been demonstrated by some researchers . Here, we report an effective route for obtaining SAN/PBT polymeric nanoblends compatibilized with MGE and the evaluation of their mechanical properties and heat distortion temperature (HDT) as a result of the concentration of the dispersed phase, the final morphology, and the proportion of MGE in the blends.…”
Section: Introductionmentioning
confidence: 94%